Development and in vitro evaluation of theophylline loaded matrix tablets prepared with direct compression - Ege, Mehmet Ali; Üstünda? Okur, Neslihan; Karasulu, Hatice Yeşim; Güneri, Tamer (Association of Pharmaceutical Teachers of India, 2016)
The objectives of the present study are to develop novel sustained release matrix tablets of theophylline and to evaluate release properties and kinetic behaviour of these tablets. The formulations have been prepared in order to improve their dissolution properties in terms of providing better oral absorption of theophylline. Therefore, the effects of the components’ nature and their proportion in the release rate were investigated. Theophylline loaded tablets were prepared with direct compression using Compritol® ATO 33 and Hydroxypropyl methylcellulose (HPMC E50) with different amounts and then they were evaluated for their in vitro drug release profiles. According the evaluation of drug release profiles, it has seen that Compritol® ATO 33 and HPMC-E50 ratio changed the release profile of theophylline. The dissolution of tablets was determined by using USP XXIII dissolution testing apparatus II. Matrix tablets were carried out in pH 4.5 phosphate buffer, as dissolution medium, for 8 h. Te-3, Te-4 and Te-7 formulations ensure the criteria of The United States Pharmacopeia XXIII for theophylline extended release capsules (Test 2 criteria, apparatus II). The release data fitted to various mathematical models such as, zero order, first order, Higuchi, Hixson Crowell and Korsmeyer-Peppas for the evaluation of the kinetics and mechanism of the drug release. The release mechanism of matrix tablets followed first order release kinetics. The results of the study indicate that new matrix tablets can be promising alternative for the other oral formulations of theophylline.
Keywords: Theophylline; Drug Release; Kinetic Evaluation; Tablet; Direct Compression